COMPARISON OF LABOR PHASES IN PAINLESS DELIVERY WITH EPIDURAL ANALGESIA AND ENTONOX ADMINISTRATION: Pharmaceutical Science-Medicine - ALIREZA KAMALI; MARYAM SHOKRPOUR; ESMAT MASHHADI; MARYAM HOSSEINZADE MORAHEM (International Journal of Life Science and Pharma Research, 2022)
Labor pain is the most severe pain a woman may experience in her life and is usually longer and more intense than expected, especially in nulliparous women. Childbirth is the most remarkable phenomenon in a woman’s life. However, parturient mothers are greatly concerned with labor pain and possible risks to their life. This study aimed to compare the duration of different labor phases in vaginal delivery after epidural or general analgesia.This study was conducted on 90 pregnant women referred to Taleghani Hospital in Arak, Iran. Participants were divided into three groups of 30, including epidural analgesia, general analgesia with Entonox gas, and control. Study groups were compared in terms of the duration of the first and second phases of labor, frequency of cesarean delivery, neonatal Apgar scores, and rate of postoperative complications (e.g., headache, nausea, vomiting, and back pain). In this study, mean age of the pregnant women was equal in all study groups, and no significant difference was observed in this regard. Mean of gestational age in the patients was 39 weeks, and the mean duration of the first labor phase was not significantly different between the study groups. Moreover, mean duration of the second labor phase was higher in the control group compared to the other patients, while it was higher in the epidural group compared to the Entonox group. According to the results of this study, painless delivery techniques, such as epidural or Entonox analgesia, do not increase the duration of the first and second phases of labor. However, use of Entonox could significantly decrease the duration of the second phase of labor.